1988
DOI: 10.1111/j.1365-2923.1988.tb00424.x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of continuing medical education on family doctor performance in office practice: a randomized control study

Abstract: A randomized controlled study was conducted to determine if specifically designed continuing medical education in the fields of cardiovascular and cancer medicine could change doctor office behaviour significantly. Thirty-one volunteer family doctors from 25 offices participated. Six (three cardiovascular and three cancer) learning objectives were defined. Two educational formats were selected as the independent variables: (1) group interaction opportunities (face-to-face and teleconference); and (2) concisely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

1992
1992
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(20 citation statements)
references
References 13 publications
0
20
0
Order By: Relevance
“…To address perceived patient expectations this study used small focus groups comprised of both patients and health care providers[28]. In another study there was an explicit attempt to involve learners by conducting a formal assessment of participant learning needs[29]. A review of audit and feedback versus alternative strategies extracted data regarding barriers to changing practice in the 12 studies identified.…”
Section: Discussionmentioning
confidence: 99%
“…To address perceived patient expectations this study used small focus groups comprised of both patients and health care providers[28]. In another study there was an explicit attempt to involve learners by conducting a formal assessment of participant learning needs[29]. A review of audit and feedback versus alternative strategies extracted data regarding barriers to changing practice in the 12 studies identified.…”
Section: Discussionmentioning
confidence: 99%
“…In this set of studies, almost two thirds (35 studies) met their objectives. Of these, 30 studies 3,6,8,10,[12][13][14][15][16][17][18][19][20]22,24,28,[31][32][33][34][35][36]40,42,44,[47][48][49][50]99 continued to meet their objectives over the long term. A further five studies 96,98,103,104,107 met objectives but did not report evaluation timing, and two studies 58,59 displayed mixed results.…”
Section: Multiple Exposuresmentioning
confidence: 99%
“…The chart audit, a careful review of information within a patient's health record using predefined criteria, is also an innovative tool used for many hospital and office quality-assurance activities. Several approaches to the use of the chart audit have been recorded (Gerbert, Countiss, and Gullion, 1983;Gullion, Adamson, and Watts, 1983;and Jennett and others, 1988). It requires peer and expert consensus on criteria and standards and provides an information baseline by which performance levels can be measured at specific times.…”
Section: Recent Innovationsmentioning
confidence: 99%
“…Practitioners can identify what their learning needs are and can measure their individual performance against those of peers in a nonthreatening, confidential manner. Jennett and others (1988) found that thirty-one family physicians in office practice could learn and adopt new behaviors in cardiovascular and cancer medicine by engaging in an innovative educational program that consisted of face-to-face and teleconference dialogues with consultants, along with the study of group performance behavior and the sharing of newsletter information. Practice issues identified for learning were discussed by family practitioners, peers, and consultant experts at designated times and through the use of newsletters.…”
Section: Recent Innovationsmentioning
confidence: 99%